An in-depth review of the UNICEF NutriDash platform, lessons learnt and future perspectives: a mixed-methods study. Issue 1 (30th January 2023) - Swift, Bethan; Imohe, Annette; Perez, Cristina H; Mwirigi, Louise
Abstract : Objectives: Robust data on nutrition are essential to realise the right to nutrition for every child. Created in 2009, UNICEF's Nutrition Dashboard (NutriDash) collects nutrition programme information from 125 countries. An in-depth review of NutriDash was conducted to understand its strengths and identify key actions to increase its effectiveness and efficiency. Methods: Adapting the Centres for Disease Control and Prevention updated guidelines for evaluating public health surveillance systems, a mixed-methods approach was used. A questionnaire was designed to capture information on key attributes of NutriDash and disseminated to UNICEF country offices for quantitative feedback on user experiences. Structured key informant interviews were held with internal and external stakeholders to gain qualitative perceptions on data generated from NutriDash. Analysis involved producing frequency distributions for the questionnaire data and performing thematic analyses on interview data. Results: A total of 53 respondents completed the questionnaire (42% response rate), representing 48 countries and good regional geographic representation. Most respondents (96%) worked in UNICEF country offices. The percentages of participants who agreed or strongly agreed with each attribute of the NutriDash system were as follows: acceptability: 71%, stability: 68%, simplicity; 63%, data quality: 60%, flexibility: 58% and usefulness: 43%. Internal and external stakeholders commented on the value of NutriDash; its use ranging from nutrition global trend monitoring for programme planning to producing reports and dashboards. Key themes derived from this review as areas for improvement included communication, access to data and data quality. Conclusions: This review has identified key themes that will inform improvements to NutriDash and form a baseline for future periodic reviews to continuously enhance the system to improve availability of timely quality nutrition programme data. UNICEF will continue to engage with countries, key partners and governments to improve the NutriDash data value chain and ensure the right to nutrition for every child.